2020
DOI: 10.1017/s0950268820000102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunisation strategies for pertussis vaccines in Jinan, China – an interrupted time-series study

Abstract: Studies in countries with high immunisation coverage suggest that the re-emergence of pertussis may be caused by a decreased duration of protection resulting from the replacement of whole-cell pertussis vaccine (WPV) with the acellular pertussis vaccine (APV). In China, WPV was introduced in 1978. The pertussis vaccination schedule advanced from an all-WPV schedule (1978–2007), to a mixed WPV/APV schedule (2008–2009), then to an all-APV schedule (2010–2016). Increases in the incidence of pertussis have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In our study, a percentage increase in hospitalization and mortality, higher frequency of cases in the dispersed rural area, and lower laboratory confirmation of cases were observed after the epidemic period compared with the epidemic period. The characteristics of pertussis cases reported during the resurgence in Colombia were similar to those in published works 32 in terms of the higher frequency of cases in children under two months of age and the occurrence of cases in adolescents and adults, whose atypical symptoms make diagnosis difficult.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, a percentage increase in hospitalization and mortality, higher frequency of cases in the dispersed rural area, and lower laboratory confirmation of cases were observed after the epidemic period compared with the epidemic period. The characteristics of pertussis cases reported during the resurgence in Colombia were similar to those in published works 32 in terms of the higher frequency of cases in children under two months of age and the occurrence of cases in adolescents and adults, whose atypical symptoms make diagnosis difficult.…”
Section: Discussionsupporting
confidence: 82%
“…6 In China, authors reported a significant reduction in diphtheria, tetanus, and pertussis incidence just after the implementation of the DwPT vaccination program. 32 With respect to diphtheria, a greater reduction in incidence was observed even before the start of vaccination, which could be related to the improvement of socioeconomic conditions of the population. After the start of vaccination, a significant, albeit slow, change in incidence was observed between the pre-and post-vaccination period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Post-slope is a continuous variable, where pre-COVID period is code 0 and COVID-impacted period takes the same value as the time variable. β1 represents the estimate at the baseline level of the outcome at time zero before the NPIs; β2 estimates the level of change in the rate immediately after the NPIs; β3 represents changes in trends after the NPIs, and εt is the error term of the model [ 13 , 14 ]. The Durbin–Watson (DW) method was used to detect and exclude the time series data stability.…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of pertussis vaccine in the 1940s and 1950s, the incidence of pertussis has declined remarkably worldwide, with 266,000 cases per year reported in the USA before the introduction of the vaccine, and only approximately 1000 cases per year reported in the 1980s after the introduction of the vaccine [ 1 ]. The incidence of pertussis in China has also declined significantly since the introduction of universal immunization programs in 1978; consequently, the incidence dropped from 100‒200 per 100,000 in the 1960s and 1970s to less than 1 per 100,000 in the late 1990s and stabilized at less than 0.2 per 100,000 from 2006 to 2010 [ 2 ]. In the past decade, however, epidemiological surveillance in developed countries such as those in Europe and the USA, where vaccine coverage is high, has revealed a gradual increase in the incidence of pertussis, known as the “resurgence of pertussis” [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%